Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.neubiorev.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

ATP-activated P2X7 receptor in the pathophysiology of mood disorders and as an emerging target for the development of novel antidepressant therapeutics

Abstract: Mood disorders are a group of psychiatric conditions that represent leading global disease burdens. Increasing evidence from clinical and preclinical studies supports that innate immune system dysfunction plays an important part in the pathophysiology of mood disorders. P2X7 receptor, belonging to the ligand-gated ion channel P2X subfamily of purinergic P2 receptors for extracellular ATP, is highly expressed in immune cells including microglia in the central nervous system (CNS) and has a vital role in mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 181 publications
(195 reference statements)
1
35
0
Order By: Relevance
“…It can be derived from the available literature as discussed in our review that P2X7Rs may be promising targets to treat MD and BD (Bhattacharya, 2018;Wei et al, 2018). However, the following three difficulties are major obstacles in developing new P2X7R antagonists for the treatment of mood disorders: (1) a number of P2X7R antagonists act in rodent receptor orthologs but not in human receptor orthologs when investigated under in vitro conditions (Bhattacharya and Biber, 2016); (2) the disease can be modeled by depressive-like states induced by applying acute or chronic inescapable stress to rodents; however, it is most likely that there is no perfect analogy with the human disease (Ribeiro et al, 2019); and (3) P2X7R antagonists have to pass the blood-brain barrier in order to exert effects in the CNS.…”
Section: P2x7r Antagonists As Possible Therapeutic Agents To Treat Momentioning
confidence: 99%
See 2 more Smart Citations
“…It can be derived from the available literature as discussed in our review that P2X7Rs may be promising targets to treat MD and BD (Bhattacharya, 2018;Wei et al, 2018). However, the following three difficulties are major obstacles in developing new P2X7R antagonists for the treatment of mood disorders: (1) a number of P2X7R antagonists act in rodent receptor orthologs but not in human receptor orthologs when investigated under in vitro conditions (Bhattacharya and Biber, 2016); (2) the disease can be modeled by depressive-like states induced by applying acute or chronic inescapable stress to rodents; however, it is most likely that there is no perfect analogy with the human disease (Ribeiro et al, 2019); and (3) P2X7R antagonists have to pass the blood-brain barrier in order to exert effects in the CNS.…”
Section: P2x7r Antagonists As Possible Therapeutic Agents To Treat Momentioning
confidence: 99%
“…The majority of compounds disclosed in the last decade are human-specific P2X7R antagonists with no or weak rodent activity but suffer from lack of robust CNS permeability. However, numerous blood-brain barrier-permeable P2X7R antagonists have been developed by Abbott, Astra-Zeneca, GlaxoSmithKline, and especially Janssen more recently (Bhattacharya, 2018;Wei et al, 2018). The Janssen compounds JNJ-47965567 (Bhattacharya et al, 2013) and JNJ-42253432 (Lord et al, 2014) demonstrated activity in rodent and human P2X7Rs, had good rat pharmacokinetic profiles, and had excellent brain penetration, when dosed subcutaneously.…”
Section: P2x7r Antagonists As Possible Therapeutic Agents To Treat Momentioning
confidence: 99%
See 1 more Smart Citation
“…4 P2X7 receptor is hypothesized to be critical in mediating brain inflammation and CNS neuron-glia signaling leading to neurodegenerative and psychiatric diseases. [5][6][7] JNJ-54175446 has been tested in single ascending dose (SAD; NCT02475148) 8 and multiple ascending dose (MAD; NCT02515955) studies in healthy subjects and is well-tolerated up to 600 mg single dose and 450 mg once daily following oral administration. The median time to achieve maximal concentration (T max ) ranged from 2-4 hours under fasted conditions, and the elimination halflife was ~ 35 hours.…”
Section: Translational Pk/pd Aided Human Pet Dose Selectionmentioning
confidence: 99%
“…In both the CNS and periphery, P2X7 receptor activation is associated with inflammasome activation leading to the production of the pro‐inflammatory cytokines, such as interleukin (IL)‐1β . P2X7 receptor is hypothesized to be critical in mediating brain inflammation and CNS neuron‐glia signaling leading to neurodegenerative and psychiatric diseases …”
mentioning
confidence: 99%